Corporate Criminal Responsibility In Cases Of Wildfires As The Legal Protection For Public (A Study In Central Kalimantan Province) - Nurahman Ramadan; Widodo Tresno Novianto; Supanto Supanto (Legal Standing : Jurnal Ilmu Hukum, 2017)
Wildfires, caused by degradation and deforestation in one decade and done by corporation who has legality in forest management, has destroyed woodland and made many losses in all aspects. In the economic development, almost all national development sources come from the management of natural resources of forest areas in Indonesia. In the 1945 constitution chapter XIV, article 33, paragraph 3, it is stated that “The land, the waters, and the natural riches comtained therein shall be controlled by the state and exploited to the geratest benefit of the people”. In fact, the weaknesses of law enforcement in forestry and environment make the transgression and deforestation keep on going.